Penerapan Pendampingan Ibu Balita Oleh Kader Kesehatan dengan Metode “Siska” Satu Ibu Satu Kader Sebagai Upaya Peningkatan Kualitas Kesehatan Balita Di Desa Glodogan - Kurniawati, Anik; Handayani, Rohmi (Yayasan Inspirasi El Burhani, 2025)
Introduction: Cadres is abbreviation hand from health center or Service Health to public in the region his work . Still height pain and death Which happen on age early need attention And support from all parties . Cadres can also play a role as the first person to discover If There is problem health in the area And quick report to power health local . Therefore​ That need done activity devotion to public with title implementation mentoring Mother toddlers by cadres health with “ siska ” method one Mother One cadre as effort improvement quality health toddler in the village the glodogan subdistrict Klaten south. Objective: 1 Increase knowledge cadre growth and development toddler, 2. implementation monitoring development toddler. Method: Activity mentoring this is the beginning with stage First that is do training on Health Cadres in do assistance to mothers toddler through a number of method that is education health , lecture , discussion , ask answer . Stage This is teach mentoring cadre to Mother toddler who to have child age 0-12 month to be continued with mentoring grow flower toddler especially in development toddlers by cadres . In mentoring This cadre Health equipped with knowledge booklet about grow flower toddler For make it easier cadre in give information related with maintenance toddler. Results: Results of activities devotion public increase knowledge about growth and development toddler from the average value pre-test 6.5 to an average post-test of 7.25 and all over toddler target has do mentoring to its development. Conclusion: mentoring Mother toddler with method One Mother One cadre can increase knowledge cadre about growth and development toddler as well as implementation mentoring development toddlers by cadres.